Umbrella effect of monitoring protocols for mammals in the Northeast US - Alessio Mortelliti; Allison M. Brehm; Bryn E. Evans (Scientific Reports)
Abstract Developing cost-effective monitoring protocols is a priority for wildlife conservation agencies worldwide. In particular, developing protocols that cover a wide range of species is highly desirable. Here we applied the ‘umbrella species’ concept to the context of ecological monitoring; specifically testing the hypothesis that protocols developed for the American marten would contextually allow detecting occupancy trends for 13 other mammalian species (i.e., an umbrella effect). We conducted a large-scale four-year camera trapping survey across a gradient of forest disturbance in Maine, USA. We sampled 197 sites using a total of 591 cameras and collected over 800,000 photographs to generate detection histories for the most common terrestrial species. By combining multi-season occupancy modelling and power analyses, we estimated the required sampling effort to detect 10%, 25% and 50% declines in the fourteen species. By conducting a spatially explicit comparison of sampling effort, we found evidence that monitoring protocols for American marten would provide an umbrella effect for up to 11 other mammal species. The capacity of the umbrella effect varied among species, with fisher, snowshoe hare, red squirrel, and black bear consistently covered under several scenarios. Our results support the application of the umbrella species concept to monitoring (here defined as ‘umbrella monitoring species’), providing empirical evidence for its use by management agencies.